Utilization Of Evidence-Based Therapy For The Secondary Prevention Of Coronary Artery Disease: Predictors And Impact Of Pharmacist-Initiated Interventions - Kassab, Yaman Walid (2013)
Over the past decades, secondary prevention has played a more and more important role in coronary artery disease management. Among the medications for long-term secondary prevention, antiplatelets, β-blockers, angiotensin-converting enzyme inhibitors (ACEIs), and statins were proven to be highly effective in reducing morbidity and mortality in coronary patients. Malaysian guidelines emphasize the continuous use of these evidence-based medications (EBMs) for long-term treatment after an acute coronary event. Despite the guideline recommendations, studies have reported an underuse of these EBMs in ACS patients. The main objectives of the current study were to: (1) quantify the prescription of EBMs at discharge following an acute coronary event and ongoing use in ambulatory care, (2) evaluate the impact of pharmacist-initiated interventions on improving the prescribing trend of secondary preventive therapies upon discharge, (3) evaluate patients’ adherence to EBMs at an average of two years after discharge, and (4) investigate the relationship between patients’ non-adherence and various predictors. This study adopted an interventional comparative methodology with three phases: pre-intervention, intervention, and follow-up phases. In the pre-intervention phase, a retrospective audit was conducted and a random sample of medical records pertaining to ACS patients admitted to Hospital Pulau Pinang during the period from January 2008 to January 2010 was chosen as the control group.